2016
DOI: 10.1111/iwj.12652
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of equimolar 50% nitrous oxide/oxygen gas premix (Kalinox®) as compared with a 5% eutectic mixture of lidocaine/prilocaine (EMLA®) in chronic leg ulcer debridement

Abstract: Chronic foot and leg ulcers are a common health problem worldwide. A mainstay of chronic ulcer therapy is sharp mechanical wound debridement requiring potent analgesia. In this prospective, controlled, single-centre, crossover design study, patients were assigned to either the administration of topical analgesia with 5% lidocaine/prilocaine cream or the inhalation of an analgesic 50% N O/O gas premix. Primary outcome parameter was level of pain at maximum wound depth during debridement as measured by a visual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Reviewing studies involving EMLA, its analgesic effect is also intense, but comparisons with our results are not feasible owing to multiple differences in how and when the effect of EMLA was evaluated in these studies. 6,8,10,[33][34][35][36][37][38][39] Thus, a clinical trial comparing sevoflurane and EMLA cream with respect to their analgesic profiles would be necessary to accurately compare their efficacy profile.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing studies involving EMLA, its analgesic effect is also intense, but comparisons with our results are not feasible owing to multiple differences in how and when the effect of EMLA was evaluated in these studies. 6,8,10,[33][34][35][36][37][38][39] Thus, a clinical trial comparing sevoflurane and EMLA cream with respect to their analgesic profiles would be necessary to accurately compare their efficacy profile.…”
Section: Discussionmentioning
confidence: 99%
“…Two small quasi-experimental studies 6,7 (n = 25 and n = 21, respectively) at moderate risk of bias reported use of lignocaine/prilocaine cream applied pre and post sharp debridement to manage pain in chronic leg ulcers. In people with moderate to severe WRP, daily application of lignocaine/ prilocaine cream prior to performing sharp debridement was well tolerated and reduced the VAS score from 75 to 21 by day ten of treatment.…”
Section: Clinical Evidencementioning
confidence: 99%
“…Approximately 90% of participants reported overall more comfort and pain relief with lignocaine/ prilocaine cream compared with the inhaled gas . Both studies 6,7 support the use of lignocaine/prilocaine cream for debridement wound pain; however, a combination of both inhaled N 2 O/O 2 and lignocaine/prilocaine cream could be an effective strategy if one treatment is not sufficient 7 (Level 2).…”
Section: Clinical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…• La administración de diversos fármacos con acción analgésica sistémica. Para el dolor moderado y ocasional: analgésicos no opioides; y para el dolor intenso y constante: opiáceos y derivados en sus diferentes formas de presentación, contribuyendo directamente al control analgésico global, aunque pueden producir efectos no deseables 7 .…”
Section: Síntesis De Los Datosunclassified